The Anti-gender and Gender-critical Roots of the Italian Anti-trans Parent Activism - Massimo Prearo (DiGeSt: Journal of Diversity and Gender Studies, 2023)
Between 2020 and 2021, the fight against the hate crimes bill proposal on discrimination and violence based on sex, gender, sexual orientation, gender identity, and disability marked a pivotal moment in the ongoing mobilization against LGBTQ+ rights in Italy. Proposed by the main center-left party, the Bill proposal encountered a strong opposition both by right-wing and by MPs of the progressive area itself. In particular, the category of gender identity was targeted as a danger, a confused notion, a trojan horse of the “gender ideology”, etc. The Bill first adopted by the Lower House was later blocked at the Senate, thanks to the decisive action of Senator Simone Pillon, a founder and member of the Italian anti-gender movement, elected in 2018 with the radical right party of the League, led by Matteo Salvini. Anti-gender groups such as ProVita & Famiglia and Family Day, who had been campaigning against "gender theory" and "LGBT ideology" for over a decade, led this battle from outside the Parliament, online and in the streets, but also inside the Senate, during the parliamentary auditions to which they were massively invited to participate